Analisis Implementasi Corporate Online Payment System PT Telekomunikasi Selular dalam Mendukung Transaksi Non Tunai Pelanggan Halo - Sugiharto, Pranowo; Tb. M Adrie Admira (Teknik Informatika Universitas Pamulang, 2025)
The rapid growth of digital payment systems has encouraged large-scale companies to adopt efficient and integrated cashless transaction mechanisms. PT Telekomunikasi Selular implemented the Corporate Online Payment System (CoPS) to support non-cash payments to Pelanggan Corporates. This study aims to analyze the implementation of CoPS and identify its benefits and challenges. A qualitative descriptive approach was applied using in-depth interviews, document analysis, and literature review. The results indicate that CoPS improves payment efficiency, accelerates financial reconciliation, and enhances transaction accuracy and transparency. However, several challenges remain, including human resource readiness, Pelanggan Corporate adaptation, and system data integration. This study concludes that CoPS plays a significant role as a supporting system for cashless transactions and corporate financial management, with strong potential to support sustainable digital transformation in corporate payment systems.